2018
DOI: 10.1002/star.201700346
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fiber, Gastric Emptying, and Carbohydrate Digestion: A Mini‐Review

Abstract: There are many checks and balances in the body that regulate the recovery of energy from sugars and starches in the presence of non-starch polysaccharides. This mini-review seeks to consider those factors, pertaining to the presence of dietary fiber that may interact with starch digestion and the absorption of sugars in the diet. Biochemical, nutritional and physiological aspects are considered. The influences of fiber in the diet are multifunctional and the layers of interaction within the stomach and small i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 52 publications
(37 reference statements)
1
27
0
Order By: Relevance
“…The Brazilian Health Regulatory Agency (Anvisa) reports that a cereal bar can be classified as a high content dietary fibers product if contains at least 6 g of fibers /100 g to act as a physiological functional fiber source, (Obrigatória, 2005) while also able reduce the risk of diseases, to be categorized as a functional product (Fuller, Beck, Salman, & Tapsell, 2016). In addition, fiber‐rich foods are indicated against intestinal disturbances (Qi, Al‐Ghazzewi, & Tester, 2018), diabetes (InterAct Consortium, 2015), atherosclerosis (Wu et al, 2003), and cancer (Kunzmann et al, 2015). In this context, the cereal bars produced have a great market perspective, emerging as a new product with functional characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…The Brazilian Health Regulatory Agency (Anvisa) reports that a cereal bar can be classified as a high content dietary fibers product if contains at least 6 g of fibers /100 g to act as a physiological functional fiber source, (Obrigatória, 2005) while also able reduce the risk of diseases, to be categorized as a functional product (Fuller, Beck, Salman, & Tapsell, 2016). In addition, fiber‐rich foods are indicated against intestinal disturbances (Qi, Al‐Ghazzewi, & Tester, 2018), diabetes (InterAct Consortium, 2015), atherosclerosis (Wu et al, 2003), and cancer (Kunzmann et al, 2015). In this context, the cereal bars produced have a great market perspective, emerging as a new product with functional characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…Some dietary fibre affects the digestion rate by reducing gastric emptying, limiting digestive enzyme activity, and restricting the rate and extent of nutrient absorption in the gut. After ingestion, dietary fibre passes through the oesophagus and stomach and reaches the small intestine followed by fermentation by the microbiota in the caecum and colon, and finally, absorption by the host (Qi, Al‐Ghazzewi, & Tester, ).…”
Section: Introductionmentioning
confidence: 99%
“…Foods rich in dietary fiber, especially soluble fiber, have been reported in several previous studies to slow gastric emptying rate [ 30 , 31 , 32 ]. This is largely a result of fiber’s high water-holding capacity and viscosity, both of which increase gastrointestinal fullness and limit the ability of food particles to enter the duodenum [ 33 , 34 ]. However, not all studies have reported such effects [ 35 , 36 ]; one study reported that consumption of 15 g of bran twice daily for four days had no effect on gastric emptying rate in healthy human subjects [ 35 ], while other studies reported that healthy human subjects who consumed high fiber products, containing either 5% cellulose or low (2.5%) or high (5%) doses of alginate or a type 3 resistant starch (retrograded amylose) exhibited accelerated gastric emptying rates [ 36 , 37 ], consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%